The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41596-018-0121-7
|View full text |Cite|
|
Sign up to set email alerts
|

Fractionation of lignocellulosic biomass to produce uncondensed aldehyde-stabilized lignin

Abstract: Lignin is one of the most promising sources of renewable aromatic hydrocarbons. Current methods for its extraction from lignocellulosic biomass-which include the kraft, sulfite, and organosolv processes-result in the rapid formation of carbon-carbon bonds, leading to a condensed lignin that cannot be effectively depolymerized into its constituent monomers. Treatment of lignocellulosic biomass with aldehydes during lignin extraction generates an aldehyde-stabilized lignin that is uncondensed and can be converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 36 publications
3
99
0
Order By: Relevance
“…Afterwards, they compared different protecting reagents (aldehydes, ketones, dimethyl carbonate, phenylboronic acid), with formaldehyde giving the highest yield (46 wt %) of phenolic monomers, followed by propionaldehyde (42 wt %) and acetaldehyde (37 wt %) . The aldehyde‐stabilized lignin could be readily selectively dissolved in an organic solvent and catalytically depolymerized to a near‐theoretical yield of phenolic monomers (40–50 wt % for a typical hardwood) …”
Section: Other Strategies For Improving the Monomer Yields And Potentmentioning
confidence: 99%
“…Afterwards, they compared different protecting reagents (aldehydes, ketones, dimethyl carbonate, phenylboronic acid), with formaldehyde giving the highest yield (46 wt %) of phenolic monomers, followed by propionaldehyde (42 wt %) and acetaldehyde (37 wt %) . The aldehyde‐stabilized lignin could be readily selectively dissolved in an organic solvent and catalytically depolymerized to a near‐theoretical yield of phenolic monomers (40–50 wt % for a typical hardwood) …”
Section: Other Strategies For Improving the Monomer Yields And Potentmentioning
confidence: 99%
“…6c and Fig. S29) 28 . This lignin-derived oil was then selectively hydrogenated to the oxygenated 2-methoxy-4propylcyclohexanol (1, having -OH and -OCH 3 retained) with suppressed deoxygenation using PtRhAu catalyst.…”
Section: Resultsmentioning
confidence: 96%
“…We further demonstrate the versatility of PtRhAu catalysts in an integrated lignin biore nery to obtain oxygenated chemicals directly from lignocellulosic biomass. We rst converted birch wood to ligninderived oils containing 4-propylsyringol (4PS) and/or 4-propylguaiacol (4PG) using aldehyde-assisted fractionation (AAF) followed by hydrogenolysis 5,28 . These lignin-derived oils were then selectively hydrogenated and funneled to a single OFG-rich chemical 2-methoxy-4-propylcyclohexanol for synthetic perfumes using our novel electrocatalysts under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although this functionalization was first reported with formaldehyde, it has since been shown that this reaction works efficiently with a large array of aldehydes. It was also notably shown that, by using a variety of multiple aldehydes, the solubility of the resulting lignins could be tuned, making them soluble in vastly different solvents from water to toluene [97][98][99]. This range of solubility could be further used to tailor lignin incorporation into several polymers.…”
Section: Reaction Of Aliphatic Hydroxyl Groupsmentioning
confidence: 99%